Association of the dietary index for gut microbiota and chronic obstructive pulmonary disease: a cross-sectional study - Ao, Ting; Huang, Yingxiu; Zhen, Peng; Hu, Ming (Frontiers in Nutrition, 2025)
BackgroundGut microbiota plays a vital role in maintaining human health. The dietary index for gut microbiota (DI-GM), which reflects the diversity of gut microbiota, has not yet been studied for chronic obstructive pulmonary disease (COPD).MethodsThis cross-sectional study analyzed data from adult participants in the 1999–2018 National Health and Nutrition Examination Survey. COPD was identified based on self-reported data. The DI-GM was calculated using dietary recall data. Multivariable logistic regression models were employed to assess the association between DI-GM and COPD. To evaluate the robustness of the association, subgroup and sensitivity analyses were applied.ResultsIncreased DI-GM was associated with a decreased prevalence of COPD (OR = 0.96; 95% CI, 0.92–0.99; P = 0.016). Greater beneficial gut microbiota scores were inversely related to the prevalence of COPD (OR = 0.95; 95% CI, 0.91–1.00; P = 0.03). Both unweighted and multiple interpolated logistic regression analyses confirmed that the relationship remained consistent. Subgroup analyses further supported the robustness of the findings.ConclusionA negative association was observed between DI-GM and the prevalence of COPD.